Preschool Child Growth and Development Examination at Pertiwi Tambak Kindergarten, Karangdowo, Klaten - Wahyuni, Sri; Hatati, Lilik; Azzahra, Alfi Halisa (WASATHON Jurnal Pengabdian Masyarakat, 2025)
Child growth and development monitoring is crucial for early detection of developmental disorders. Indonesian Survey of Nutritional Status (SKI) data shows that stunting rates in 2023 were 21.5%, with increasing trends in wasting (8.5%) and overweight (4.2%) rates among toddlers. This community service activity aimed to assess growth and development status among preschool children and identify potential developmental disorders early through systematic screening at Pertiwi Tambak Kindergarten. The activity was conducted on May 16, 2024, involving 20 preschool children aged 54-72 months. Growth assessment included anthropometric measurements (weight, height), while development was evaluated using the Indonesian Pre-screening Development Questionnaire (KPSP). Participants comprised 15 males (75%) and 5 females (25%). Developmental screening revealed 19 children (95%) with appropriate development and 1 child (5%) requiring further evaluation, who was subsequently diagnosed with autism spectrum disorder. Most children showed age-appropriate development, indicating the importance of early screening programs in educational settings for timely intervention and the crucial role of collaboration between parents, teachers, and healthcare professionals in optimal child development monitoring.